Carbon black nanoparticles induce pulmonary fibrosis through NLRP3 inflammasome pathway modulated by miR-96 targeted FOXO3a. (February 2020) - Zhou, Lixiao; Li, Peiyuan; Zhang, Mengyue; Han, Bin; Chu, Chen; Su, Xuan; Li, Binghua; Kang, Hui; Ning, Jie; Zhang, Boyuan; Ma, Shitao; Su, Dong; et al.
Abstract: Carbon black nanoparticle (CBNP) is a core constituent of air pollutants like fine particulate matter (PM2.5) as well as a common manufactural material. It was proved to pose adverse effects on lung function and even provoke pulmonary fibrosis. However, the underlying mechanisms of CBNPs-induced pulmonary fibrosis remain unclear. The present study aimed to investigate the mechanism of fibrotic effects caused by CBNPs in rat lung and human bronchial epithelial (16HBE) cells. Forty-nine male rats were randomly subjected to 7 groups, means the 14-day exposure group (30 mg/m 3 ), the 28-day exposure groups (5 mg/m 3 and 30 mg/m 3 ), the 90-day exposure group (30 mg/m 3 ) and their respective controls. Rats were nose-only-inhaled CBNPs. 16HBE cells were treated with 0, 50, 100 and 200 μg/mL CBNPs respectively for 24 h. Besides, Forkhead transcription factor class O (FOXO)3a and miR-96 overexpression or suppression 16HBE cells were established to reveal relative mechanisms. Our results suggested CBNPs induced pulmonary fibrosis in time- and dose-dependent manners. CBNPs induced persisting inflammation in rat lung as observed by histopathology and cytology analyses in whole lung lavage fluid (WLL). Both in vivo and in vitro, CBNPs exposure significantly increased the expression of NLRP3 inflammasome, accompanied by the increased reactive oxygen species (ROS), decreased miR-96 and increased FOXO3a expressions dose -and time-dependently. MiR-96 overexpression or FOXO3a suppression could partially rescue the fibrotic effects through inhibiting NLRP3 inflammasome. Conclusively, our research show that CBNPs-induced pulmonary fibrosis was at least partially depended on activation of NLRP3 inflammasome which modulated by miR-96 targeting FOXO3a. Graphical abstract: Image 1 Highlights: CBNPs-induced pulmonary fibrosis might be linked with persistent lung inflammation. The potential mechanism might relate with NLRP3 inflammasome activation. NLRP3 inflammasome activation might be modulated by miR-96 targeted FOXO3a.